2022
DOI: 10.1186/s12884-022-04905-7
|View full text |Cite
|
Sign up to set email alerts
|

Maternal lipid levels in early pregnancy as a predictor of childhood lipid levels: a prospective cohort study

Abstract: Background Maternal lipid levels in early pregnancy are associated with maternal health and foetal growth. It is however unclear if maternal lipids in early pregnancy can be used to predict childhood lipid levels. The aim of this study is to assess the association between maternal and offspring childhood lipid levels, and to investigate the influence of maternal BMI and diet on these associations. Methods This study included 2692 women participatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 70 publications
3
4
0
Order By: Relevance
“…In this study, we found significantly higher concentrations of total cholesterol, LDL cholesterol, HDL cholesterol, non-HDL cholesterol, and apolipoprotein B in girls compared to boys. These findings are in agreement with previous findings for total cholesterol, LDL cholesterol, and HDL cholesterol, 12 , 23–26 but have not been shown for non-HDL and apolipoprotein B previously. However, in this study, we observed lower mean and median concentrations of total cholesterol, LDL cholesterol, HDL cholesterol, and triglycerides in umbilical cord blood compared to concentrations reported in previous studies, 23–25 which may be due to differences in ethnicities, and lower number of individuals (ranging from 206 to 442) in the previous studies of Iranian and Polish origin.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, we found significantly higher concentrations of total cholesterol, LDL cholesterol, HDL cholesterol, non-HDL cholesterol, and apolipoprotein B in girls compared to boys. These findings are in agreement with previous findings for total cholesterol, LDL cholesterol, and HDL cholesterol, 12 , 23–26 but have not been shown for non-HDL and apolipoprotein B previously. However, in this study, we observed lower mean and median concentrations of total cholesterol, LDL cholesterol, HDL cholesterol, and triglycerides in umbilical cord blood compared to concentrations reported in previous studies, 23–25 which may be due to differences in ethnicities, and lower number of individuals (ranging from 206 to 442) in the previous studies of Iranian and Polish origin.…”
Section: Discussionsupporting
confidence: 93%
“… 11 Maternal lipid concentrations in early pregnancy have been shown to associate with offspring venous blood concentrations in later childhood (age 6 and 10 years). 12 Dyslipidaemia in childhood and adolescence is associated with dyslipidaemia in adulthood, fatty streaks in the aorta, and increased intima-media thickness 13–17 with FH as the classical example for ASCVD development in early adulthood. 18 However, if lifestyle interventions and treatments are initiated during childhood, the risk of ASCVD can be minimized and become similar to the background population—observations that emphasize the importance of early interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Results from this same cohort further showed that maternal early gestational lipid profile is associated with offspring's lipid profile at age 5–6 years [6]. Similar to findings from a Norwegian study in 61 mother-children pairs [42], in the ongoing population-based Generation R study, lipid profile in early pregnancy ( n = 2692, median 13.2 weeks) was associated with the lipid profile of children at 6 and 10 years after pregnancy [43 ▪▪ ], independent of maternal BMI and diet.…”
Section: Dyslipidemia During Pregnancy: Consequences For the Offspringsupporting
confidence: 77%
“…We have previously found a positive association between maternal prenatal HDL-C and newborn HDL-C level [ 34 ]. Hence, maternal mid-pregnancy TC and HDL-C levels probably affect fetal TC and HDL-C levels but also possibly offspring TC and HDL-C later in childhood [ 48 , 49 ]. High offspring LDL-C level may increase and high offspring HDL-C level may decrease the supply of cholesterol to peripheral cells [ 50 ], which in theory may affect the offspring’s development or epigenetic pattern, and subsequent body growth [ 5 , 20 22 ].…”
Section: Discussionmentioning
confidence: 99%